2017
DOI: 10.1007/s10791-017-9299-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvements for search systems using an integrated cache of lists + intersections

Abstract: Modern information retrieval systems use several levels of caching to speedup computation by exploiting frequent, recent or costly data used in the past. Previous studies show that the use of caching techniques is crucial in search engines, as it helps reducing query response times and processing workloads on search servers. In this work we propose and evaluate a static cache that acts simultaneously as list and intersection cache, offering a more efficient way of handling cache space. We also use a query reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Three-level architectures store in the additional level of the cache the precomputed intersections of posting lists [31,45,47]; this improves the processing of more complex queries such as AND or phrase queries. Ozcan et al [34] presented an even more sophisticated cache consisting of five levels for storing query results, precomputed scores, posting lists, precomputed intersections of posting lists, and documents.…”
Section: Related Workmentioning
confidence: 99%
“…Three-level architectures store in the additional level of the cache the precomputed intersections of posting lists [31,45,47]; this improves the processing of more complex queries such as AND or phrase queries. Ozcan et al [34] presented an even more sophisticated cache consisting of five levels for storing query results, precomputed scores, posting lists, precomputed intersections of posting lists, and documents.…”
Section: Related Workmentioning
confidence: 99%
“…Though the authors concluded that the inference retrieval method was more effective compared to a general retrieval method, the inference analysis lacked relevant judgement while choosing queries. Tolosa et al (2017) lately used information retrieval systems at unique stages to speed up computations. The authors proposed a static cache and evaluate its space for query executions and differences to reveal between raw and compressed forms.…”
Section: Information Retrieval Frameworkmentioning
confidence: 99%
“…A three-level cache that contains the proposed intersection cache was proposed, and improved results were obtained. Tolosa et al [9] studied the integrated cache that combines the posting list cache and the intersection cache in a single stored space. The term pairs are structured to make an efficient use of the cached space in order to maximize the hit ratio.…”
Section: Related Workmentioning
confidence: 99%
“…A number of caching techniques used in search engines have been studied so far. Current search engines often use five popular caching techniques, namely result cache [1]- [5], posting list cache [6], [7], intersection cache [8], [9], snippet cache [10], and document cache [11]. The well-known cache replacement strategies include LRU, LFU and LCU [12].…”
Section: Introductionmentioning
confidence: 99%